"Close-to-ideal" tumor boron targeting for boron neutron capture therapy is possible with "less-than-ideal" boron carriers approved for use in humans - Schwint, Amanda Elena; Trivillin, Verónica Andrea (Future Science Group, 2015)
Fil: Schwint, Amanda Elena. Comisión Nacional de Energía Atómica. Gerencia de Area de Aplicaciones de la Tecnología Nuclear. Gerencia de Radiobiología (Centro Atómico Constituyentes); Argentina